P451 Long-term surgical outcome of ileal pouch-anal anastomosis when used for well-defined Crohn's disease. (16th January 2018) - Mandel, D; Zaghiyan, K; Fleshner, P
Abstract: Background: Crohn's disease (CD) is considered a contraindication to ileal pouch-anal anastomosis (IPAA). A preliminary study from our group in 17 patients showed the intentional use of IPAA in CD compared with ulcerative colitis patients was associated with a higher incidence of postoperative recurrent disease but no significant difference in pouch failure (Le Q et al., Inflamm Bowel Dis 2013;19:30–6). Using a larger sample size, this study sought to extend these findings in a larger patient cohort followed over a longer postoperative time. Methods: A prospective inflammatory bowel disease registry was queried for patients with pre-operative CD undergoing IPAA. Patients were considered to have CD before surgery based on a history of perianal disease, small-bowel disease, perianal disease, pre-treatment skip lesions or non-crypt associated granuloma. Patients were prospectively assessed for pouchitis or CD. Pouchitis (acute and chronic), postoperative CD (pouch inflammation into the afferent limb or pouch fistula) or pouch failure (need for permanent diversion) were assessed. Results: Forty patients with pre-operative CD were identified. CD was diagnosed based on perianal disease ( n = 13; 32%), small-bowel disease ( n = 10; 25%), pre-treatment skip lesions ( n = 10; 25%) and noncaseating granuloma ( n = 7; 18%). Indications for surgery were medically unresponsive disease ( n = 37;93%) or cancer/dysplasia ( n = 3; 8%). After a median follow-up time of 61 (range 2–196) months, pouchitis developed in 11 (28%) patients (acute pouchitis ( n = 9), chronic pouchitis ( n = 2)). Seventeen (43%) patients developed postoperative recurrent CD in the afferent limb ( n = 9), pouch fistulising disease ( n = 4) or perianal disease ( n = 4). Only one patient (3%) required faecal diversion. The incidence of recurrent CD over time is shown in the figure. Conclusions: This largest-ever report examining the intentional use of IPAA in well-defined CD has shown a high (43%) incidence of postoperative disease. However, there is a low (3%) incidence of ultimate pouch failure. Highly motivated patients with colorectal CD involving the more proximal and/or distal gastrointestinal tract may wish to undergo IPAA and avoid a definitive end ileostomy.